2009
DOI: 10.2746/042516409x391015
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic retrospective study of the caudal cervical articular process joints in the horse

Abstract: The data in this study support that the size of the caudal cervical APJ at the level of C5-C6, appear to increase with age, but this enlargement may not be significant. Enlargement cannot be associated with breed, sex or discipline of the horse at present, and specific grades and therefore degree of enlargement, cannot necessarily be assumed to be the cause of neurological deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 14 publications
7
92
4
4
Order By: Relevance
“…In a recent study an objective grading system was introduced for assessment of radiographic changes associated with the caudal articular process joints on lateral views (Down and Henson 2009). In this study the authors demonstrated that an increase in size of the articular process joints of the caudal cervical APJ (mainly C5/6), may be age related and that enlargement of process joints (both C5/6 and C6/7) should not be assumed to be abnormal in all cases.…”
mentioning
confidence: 85%
“…In a recent study an objective grading system was introduced for assessment of radiographic changes associated with the caudal articular process joints on lateral views (Down and Henson 2009). In this study the authors demonstrated that an increase in size of the articular process joints of the caudal cervical APJ (mainly C5/6), may be age related and that enlargement of process joints (both C5/6 and C6/7) should not be assumed to be abnormal in all cases.…”
mentioning
confidence: 85%
“…The diagnosis cannot be made upon radiographic findings alone because similar findings are described in horses without clinical symptoms (Down and Henson 2009). Therefore, the definitive diagnosis has to be validated based on clinical findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies stated that CVCM can be caused by osteoarthritis, however, the main cause of this abnormality is unknown (Levine et al 2007), and 50 % of asymptomatic adult horses have unilateral or bilateral surface changes of the facet joints and irregular enlargement of the articular processes of the caudal cervical vertebrae (Down andHenson 2009, Dyson 2011). The diagnosis cannot be made upon radiographic findings alone because similar findings are described in horses without clinical symptoms (Down and Henson 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies gilt vor allem für spondylarthrotische Erkrankungen der Facettengelenke der Halswirbelsäule. Jedoch können bei einem Großteil der klinisch unauffälligen Pferde röntgenologisch sichtbare arthrotische Prozesse, insbesondere im Bereich C6/C7 beobachtet werden (Down und Henson 2009, Whitwell und Dyson 1987.…”
Section: Introductionunclassified